Leadership style and job satisfaction as correlates of turnover intentions among library personnel in private university libraries in South-South, Nigeria - Rosemary Anwuli Odiachi (IJoLIS, 2023)
Purpose: The study looked at leadership style and job satisfaction as correlates of the turnover intentions among library personnel in private university libraries in South-South, Nigeria. Design/ methodology/approach: The study used a correlational survey design with 113 library staff as the population. The data collection instrument was a questionnaire created by the researcher. A sum of 103 copies of the 113 copies of the questionnaire were obtained, resulting in a 91.15% response rate. The descriptive statistics of Pearson Product Moment Correlational Coefficient (r) (PPMCC) were utilized to analyse data collected from the study questions